Islamic Theological Perspective on Pancasila Textbook in Higher Education - Khalimi khalimi; Abu Khaer (TARBIYA: Journal of Education in Muslim Society, 2020)
AbstractThis reasearch aims to describe the reconstruction of the worldview of Islamic theology within the Pancasila course textbook used at Islamic institutes of higher education. The authors’ observation, research, and knowledge indicate that the majority of students taking compulsory subjects in both general and Islamic tertiary institutions tend to assume that there is no link between the teachings of Pancasila and the teachings of Islamic theology. On the contrary, according to the formulators of Pancasila and the founding fathers of Indonesia, Pancasila is an essence of religious teachings. For example, Soekarno explained that the reason for naming the nation's philosophy Pancasila was because it was inspired by the five pillars of Islam. This research is qualitative in nature by exploring and examining available data in more depth and detail. This type of research places emphasis on library research. Up to the present time, various findings and discussions seem to indicate that the virtuous theological values of Pancasila, with its many variants of scientific studies, are discussed and studied separately from the ‘life and death’ struggle of its theological concept throughout the history of Pancasila to become the nation’s philosophical foundation. Pancasila education has long been considered as a pure knowledge free from any practical involvement of its initiators. The theological concept of Pancasila, which later evolved to become part of subject material in Pancasila Education, demonstrated that it was, in fact, played a role in the zeitgeist, which caused quite a commotion stir during its formulation days.AbstrakPenelitian bertujuan untuk menggambarkan rekonstruksi pandangan dunia teologi Islam dalam buku ajar kursus Pancasila yang digunakan di lembaga pendidikan tinggi Islam. Pengamatan, penelitian, dan pengetahuan penulis menunjukkan bahwa mayoritas siswa yang mengambil mata pelajaran wajib di lembaga pendidikan umum dan Islam cenderung berasumsi bahwa tidak ada hubungan antara ajaran Pancasila dan ajaran teologi Islam. Sebaliknya, menurut perumus Pancasila dan para pendiri bangsa Indonesia, Pancasila adalah inti dari ajaran agama. Misalnya, Soekarno menjelaskan bahwa alasan penamaan filsafat bangsa Pancasila adalah karena ia terinspirasi oleh lima rukun Islam. Penelitian ini bersifat kualitatif, dengan mengeksplorasi dan memeriksa data yang tersedia secara lebih mendalam dan terperinci. Jenis penelitian ini menekankan pada penelitian kepustakaan. Hingga saat ini, berbagai temuan dan diskusi tampaknya mengindikasikan bahwa nilai-nilai teologis Pancasila yang saleh, dengan banyak varian studi ilmiahnya, dibahas dan dipelajari secara terpisah dari perjuangan 'hidup dan mati' dari konsep teologisnya sepanjang sejarah Pancasila menjadi landasan filosofis bangsa. Pendidikan Pancasila telah lama dianggap sebagai pengetahuan murni yang bebas dari keterlibatan praktis penggagasnya. Konsep teologis Pancasila, yang kemudian berkembang menjadi bagian dari materi pelajaran dalam Pendidikan Pancasila, menunjukkan bahwa itu sebenarnya memainkan peran dalam zeitgeist, yang menyebabkan keributan yang cukup besar selama hari-hari perumusannya.How to Cite: Khalimi., khaer, A. (2020). Islamic Theological Perspective on Pancasila Textbook in Higher Education. TARBIYA: Journal of Education in Muslim Society, 7 (1), 102-118. doi:10.15408/tjems.v7i1.16718.